2017
DOI: 10.1016/j.jogn.2017.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition of Black Women During Pregnancy

Abstract: Objective To examine the consistency and adequacy of nutritional intake in a population of Black women in the second and third trimesters of pregnancy. Design This was a longitudinal descriptive study. Data were collected from women with low-risk pregnancies at 22–24 week prenatal visits and two subsequent visits. Setting Participants were recruited from urban prenatal clinics in one city in the Northeastern United States. Participants Pregnant women who self-identified as Black (N=195) Methods A 24-ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 50 publications
(51 reference statements)
0
3
0
Order By: Relevance
“…Although we did not assess dietary iron intake and supplements in the current study, it is plausible that disparity in nutrient intakes exists between white and ethnic minority women. Previous studies have demonstrated that iron intake in pregnancy is inadequate in ethnic minority women [ 33 , 34 ]. As ethnic minority groups experience higher rates of obesity, further studies exploring ethnic disparities in markers of maternal iron status are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Although we did not assess dietary iron intake and supplements in the current study, it is plausible that disparity in nutrient intakes exists between white and ethnic minority women. Previous studies have demonstrated that iron intake in pregnancy is inadequate in ethnic minority women [ 33 , 34 ]. As ethnic minority groups experience higher rates of obesity, further studies exploring ethnic disparities in markers of maternal iron status are warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Inadequate diets that lead to nutrient deficiencies as well as lack of energy intake (EI) can have a substantial impact on pregnancy outcomes and neonatal health. Energy and nutritional restriction disrupt proper fetal development and may result in disease persisting into the individual's subsequent life, including type II diabetes, hypertension, and cardiovascular disease [3]. Therefore, understanding the relation between maternal nutrition and pregnancy outcomes may provide a basis for nutritional interventions that will improve birth outcomes and long-term quality of life [4].…”
Section: Introductionmentioning
confidence: 99%
“…One other longitudinal study found that fruit intake in first-time mothers decreased compared to non-mothers (33). However, a common finding among all these studies, which is also confirmed by Belgian food consumption data, is that intake of healthy food groups such as fruits and vegetables for most women appear to be below the recommended daily intake (33,(35)(36)(37)(38)(39)(40)(41). The pregnant women from our sample had a fruit intake of 206 g/day which is indeed below the recommended 250 g/day.…”
Section: Discussionmentioning
confidence: 76%